2018
DOI: 10.5455/ajpbp.20180616012821
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic oral toxicity studies of the leaves aqueous extract of Clerodendrum umbellatum Poir. on mice

Abstract: Aim: The schistosomicidal activity of Clerodendrum umbellatum leaves aqueous extract (CuAE) has been previously demonstrated. The present study was performed to establish the acute and sub-chronic oral toxicity profile of CuAE in mice. Methods: For acute oral toxicity study, CuAE was administered per os to female mice at a single dose of 2,000 mg/kg. Animals were observed for 14 days in order to identify the signs of toxicity or death. In the repeated dose 28-day oral toxicity study, the extract was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The data showed slight changes in the mice's body weight (Figure -4). Body-weight variation is the first sign of toxicity and a substantial indication of drug and chemical adverse effects in animals [22,23]. In this study, there were no statistically significant differences in body weight among groups, indicating no toxic effect of biochemical substances contained in PSPY.…”
Section: Sub-chronic Oral Toxicity Studymentioning
confidence: 44%
“…The data showed slight changes in the mice's body weight (Figure -4). Body-weight variation is the first sign of toxicity and a substantial indication of drug and chemical adverse effects in animals [22,23]. In this study, there were no statistically significant differences in body weight among groups, indicating no toxic effect of biochemical substances contained in PSPY.…”
Section: Sub-chronic Oral Toxicity Studymentioning
confidence: 44%
“…However, little is done to carry out toxicity evaluation of such herbal medicines. The toxicity evaluation of herbal medicines is necessary because evidence has shown that some herbal bioactive agents have negative effects contributed with secondary metabolites [3,[6][7][8][40][41][42][43] Our study aimed to determine toxicity of root and leaf methanolic extracts of T. vogelii regarding the reported ethnopharmacological potentiality. Explicitly, the lethality (LD 50 ) and sub-acute toxicity of methanolic leaf and root extracts of T. vogelii were evaluated using the animal model.…”
Section: Resultsmentioning
confidence: 99%
“…There is enough evidence that shows that herbal medicines can have negative effects on animals and humans [3,[7][8][9]. Thus, the common belief that those concoctions from medicinal plants are natural and generally regarded as safe (grass) does not always hold true.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that alterations in the hematological parameters have high predictive value for toxicity (Jatsa et al, ; Mukinda & Syce, ). Thus, the results in this study supported that the SMBT is innocuous.…”
Section: Resultsmentioning
confidence: 99%